Роль парламенту України щодо розвитку інституту примусового відчуження приватної властності, зумовленого суспільною необхідністю - Клименко, О.М. (Держава і право, 2012)
Аналізується роль Верховної Ради України стосовно розвитку конституційно-правового забезпечення інституту примусового відчуження об’єктів права приватної власності, зумовленого суспільною необхідністю. Анализуется роль Верховной Рады Украины относительно развития конституционно-правового обеспечения института принудительного отчуждения объектов правачастной собственности, обусловленного общественной необходимостью. The problem of the formation in Ukraine of an Institute of the Private Property Expropriation due to a Cause of Public Necessity requires the research of its constitutional development by the public authorities according to the Constitution of Ukraine. The article analyzes the role of the Verkhovna Rada of Ukraine in the development of the constitutional and legal provision for the institute of private property expropriation due to a cause of public necessity.